2016
DOI: 10.3892/mco.2016.941
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the association between perineural invasion and clinical and histopathological features of cervical cancer

Abstract: Abstract. Perineural invasion (PNI) has been investigated as a new prognostic factor in a number of carcinomas. However, studies on PNI in cervical cancer are limited, and inconsistent conclusions have been reported by different groups. The aim of the present study was to analyze the relationship between perineural invasion (PNI) and clinical and histopathological features of cervical cancer, and to evaluate the clinical significance of PNI of cervical cancer. Retrospective review identified 206 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…or the presence of thrombus adherent to intravascular tumor. Although LVI is a poor prognostic factor in different cancers, it is not included into the staging systems for PTC [14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…or the presence of thrombus adherent to intravascular tumor. Although LVI is a poor prognostic factor in different cancers, it is not included into the staging systems for PTC [14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Among the most frequently used staging systems for estimating the prognosis and risk of recurrence in thyroid carcinomas are those developed by the Union for International Cancer Control (UICC) and American Joint systems consistently include clinicopathological parameters, however, factors such as age, gender, tumor type and size, extracapsular extension, lymph nodes, lymphovascular invasion (LVI), and distant metastasis are not all covered by a single staging system [7][8][9][10][11][12][13]. Although LVI is a poor prognostic factor for numerous cancers, including laryngeal, uterine, endometrial, colorectal, cervical, bile duct, and vulvar cancer, none of the staging systems include LVI in staging of thyroid carcinomas [14][15][16][17][18][19][20]. In a clinical series conducted by Ieni et al [21], 295 PTC patients (8 of them with a newly described entity -micropapillary/hobnail variant [MPHC]) were evaluated and the authors concluded that the prognosis of MPHC-PTC tumors was better compared to the other groups, possibly due to a lower rate of vascular invasion in this group [21].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported that perineural spread of cervical cancer is associated with depth of stromal invasion, tumour size, invasion of the parametrium and lymphovascular space and lymph node metastasis 6. Wei et al have shown that the perineural spread in cervical cancer is associated with lymphovascular space invasion and lymph node metastasis 7. The perineural spread in the lumbosacral plexus leads to the diffuse thickening of the nerve plexus, giving appearance of ‘trident’ on the CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has shown that PNI in cervical cancer is associated with other pathology risk features, and other studies have shown that it is a predictor of poor prognosis. [ 1 2 3 ] These findings highlight the importance of clarifying the molecular mechanism of PNI.…”
mentioning
confidence: 94%